Treatment of Hospital wastewater with submerged aerobic fixed film reactor coupled with tube-settler. (January 2022) - Khan, Nadeem A.; Bokhari, Awais; Mubashir, Muhammad; Klemeš, Jiří Jaromír; El Morabet, Rachida; Khan, Roohul Abad; Alsubih, Majed; Azam, Mudassar; Saqib, Sidra; Mukhtar, Ahmad; Koyande, Apurav; Show, Pau Loke
Abstract: In this study, Hospital wastewater was treated using a submerged aerobic fixed film (SAFF) reactor coupled with tubesettler in series. SAFF consisted of a column with an up-flow biofilter. The biological oxygen demand (BOD)5, chemical oxygen demand (COD), nitrate and phosphate were the chosen pollutants for evaluation. The pollutants removal efficiency was determined at varying organic loading rates and hydraulic retention time. The organic loading rate was varied between 0.25 and 1.25 kg COD m −3 d −1 . The removal efficiency of SAFF and tubesettler combined was 75 % COD, 67 % BOD and 67 % phosphate, respectively. However, nitrate saw an increase in concentration by 25 %. SAFF contribution in the removal of COD, BOD5 and Phosphate was 48 %, 46 % and 29 %, respectively. While for accumulation of nitrate, it was responsible for 56%, respectively. Tubesettler performed better than SAFF with 52 %, 54 % and 69 % reduction of COD, BOD5 and phosphate, respectively. But in terms of nitrate, tubesettler was responsible for 44 % accumulation. The nutrient reduction decreased with an increase in the organic loading rate. Nitrification was observed in the SAFF and tubesettler, which indicated a well-aerated system. An anaerobic unit is required for completing the denitrification process and removing nitrogen from the effluent. The better performance of tubesettler over SAFF calls for necessitates extended retention time over design criteria. Further studies are beneficial to investigate the impact of pharmaceutical compounds on the efficiency of SAFF. Graphical abstract: Image 1 Highlights: Hospital wastewater was treated using submerged aerobic fixed film (SAFF). The organic loading rate was varied between 0.25 and 1.25 kg COD/m 3 d. COD removal was 48 % and 51 % for SAFF and tubesettler. BOD5 removal efficiency for SAFF and tubesettler was 40 % and 46 %, respectively. Anaerobic unit is additionally required for the denitrification process.